Analisis Pengakuan Pendapatan Dan Pengukuran Pendapatan Berdasarkan PSAK No. 72 Pada PT Semen Indonesia Logistik - Fitriana, Elicia Nur; Musyarofah, Siti (ITB AAS Indonesia Surakarta, 2024)
One of the main indicators for determining profit is revenue, so it is important to use an appropriate method to recognize and measure transactions accurately. The purpose of this study is to determine how PT Semen Indonesia Logistik measures and recognizes revenue, and compares it with the standards set out in PSAK No. 72. Data collected through interviews shall be reviewed and evaluated in compliance with the terms of the business. This study found and concluded that PT Semen Indonesia Logistik has complied with PSAK No. 72 in terms of measurement and recognition. Revenue is recognised upon contract execution and is recorded on an accrual basis. Calculating revenue by using the unit of fair value obtained or receivable, how much revenue or expense is determined based on the rate agreed in the agreement. Keywords: PSAK No. 72, Revenue recognition and revenue measurement